(untitled) - Hattangadi, A. A. (New York, 2005)
Monitoring and predictive maintenance methods are not reliable enough in indicating certain important problems in manufacturing equipment, such as cracking of power transmission components, inadequate lubrication of parts, and excessive cutting edge wear of a tool or die. These problems are best dealt with at the design stage. Plant and Machinery Failure Prevention is based on the premise of “Zero-Failure Performance”. The book introduces the general features and investigative methods at the design phase for determining failures in mechanical components such as: Flat Belt Failures, Vee-belt Failures, Pulley Failures, Gear Failures, Steel Wire Rope Failures, Spring Failures, and Gasket Failures.
Keywords: Reliability (Engineering),Sự vận hành (máy)